2022
DOI: 10.1186/s12884-022-04511-7
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live birth rates for low-prognosis women over 5 years or 9 frozen-thawed embryo transfer cycles

Abstract: Background For heterogeneous populations of low-prognosis women, it remains unclear as to how long individuals should continue undergoing ART when attempting to have a baby, as there have been insufficient studies to date tracking the cumulative live birth rates (CLBRs) for these women over the entire course of their ART treatment, particularly over extended time periods. Methods This was a retrospective analysis of 17,698 women at a tertiary care … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Chen et al. found in their study that the CLBR showed a significant upward trend with the prolongation of time or the increase in the number of FET ( 33 ). This suggests that, although older high-AMH group patients may have decreased CPR and LBR due to decreased oocyte quality as they get older, with the increase in the number of transplantation cycles, they may achieve cumulative outcomes comparable to those in young patients.…”
Section: Discussionmentioning
confidence: 95%
“…Chen et al. found in their study that the CLBR showed a significant upward trend with the prolongation of time or the increase in the number of FET ( 33 ). This suggests that, although older high-AMH group patients may have decreased CPR and LBR due to decreased oocyte quality as they get older, with the increase in the number of transplantation cycles, they may achieve cumulative outcomes comparable to those in young patients.…”
Section: Discussionmentioning
confidence: 95%
“…The COX regression analysis confirmed that in FET cycles, POSEIDON criteria was an independent factor positively associated with CLBR. Until now, only one large cohort study on CLBR in FET cycles was published which analyzed the CLBR within 5 years or 9 FET cycles in groups based on POSEIDON criteria [ 14 ]. The CLBR over 5 years estimated by optimistic analytical method was 0.75 (0.71–0.78) in POSEIDON group 3, almost the same as that of control group with 0.79 (0.78–0.80) and much higher than 0.41 (0.37–0.46) in POSEIDON group 4.…”
Section: Discussionmentioning
confidence: 99%
“…The COX regression analysis con rmed that in FET cycles, POSEIDON criteria was an independent factor positively associated with CLBR. Until now, only one large cohort study on CLBR in FET cycles was published which analyzed the CLBR within 5 years or 9 FET cycles in groups based on POSEIDON criteria [14]. The CLBR over 5 years estimated by optimistic analytical method was 0.75 (0.71-0.78) in POSEIDON group 3, almost the same as that of control group with 0.79 (0.78-0.80) and much higher than 0.41 (0.37-0.46) in POSEIDON group 4.…”
Section: Interpretation Of Ndingsmentioning
confidence: 99%